Effect of Distilled Greywater, with and without Boiling, on the Germination of Solanum Lycopersicum (Journal SCIENCEVOLUTION, 2025)
Water scarcity is a critical problem today. This study analyzed the effect of distilled greywaters, with and without boiling, on Solanum lycopersicum germination, using a glass-based DSSE and a parabolic mirror DSCE to treat domestic greywater. pH, conductivity, and turbidity of the distilled water were characterized, and germination was evaluated in Petri dishes for the two treatments (DSSE, DSCE) and a control, using a randomized design with 3 replications. Results showed yields of 30.8 ml/h and 216.667 ml/day, respectively. DSSE improved pH (6.763), while DSCE reduced conductivity from 1698 to 2.208 µS/cm, proving better than DSSE (331.400 µS/cm). DSCE turbidity was null and DSSE turbidity was 1.505 NTU. The germination index for DSSE was higher than for DSCE and the control, with a neutral optimum pH. DSSE has greater influence on Solanum lycopersicum germination due to its neutral pH, despite lower solids removal. DSCE improves physical quality but acidifies the water.
Keywords: Solar Distillation; Germination Index; Distiller; Greywater Distillation; Solanum lycopersicum